Teacher Performance Development Through Academic Supervision Post Covid-19 - Hotmaida Sidabutar; Yuniarto Mujisusatyo; Wanapri Pangaribuan; Isli Iriani Indah Pane (UNIVERSITAS PAKUAN, 2023)
This study aims to develop teacher performance through analysis of post-covid-19 academic supervision in Santa Lucia Sei Rotan Private Middle School teachers and to determine teacher performance skills in developing the quality of education after supervision is held. The type of research used is Classroom Action Research. The research method used is the Kemmis and Taggart model using 4 stages, namely planning, action, observation, and reflection. The location of this research is Santa Lucia Sei Rattan Private Middle School, Percut Sei Tuan, Deli Serdang, North Sumatra. Methods of data collection using interviews, observation, and questionnaires. The data analysis technique uses the Miles and Huberman interactive analysis model. Data analysis was carried out with the following steps: data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that academic supervision can improve teacher performance. The results obtained from design experts and material experts are very good. This is evidenced by the effectiveness test of academic supervision at Santa Lucia Sei Rotan Middle School, which received very good scores. Based on these data it can be concluded that teacher performance through post-covid-19 academic supervision is feasible or valid and appropriate to be used in improving teacher performance, especially in the Santa Lucia Sei Rotan Middle School environment.